The delivery of intergenerational programmes in the nursing home setting and impact on adolescents and older adults: A mixed studies systematic review. (September 2022) - Laging, Bridget; Slocombe, Grace; Liu, Peiyuan; Radford, Katrina; Gorelik, Alexandra
Abstract: Background: Interventions to support a more "age friendly" world are a key objective set out by the World Health Organization with health and wellbeing benefits being increasingly identified for both young and old. Whilst multiple studies have explored intergenerational engagement between kindergarten aged children and older adults, there is limited collective knowledge of programme design and the potential impact that these programmes have on adolescents engaging with older adults in the nursing home setting. Objectives: The aims of this systematic review were to: a) examine intergenerational programme development and delivery in the nursing home setting and b) report on the impact of intergenerational engagement on adolescents and older adults. Design: A systematic mixed studies review of intergenerational programmes targeting adolescents and older adults. Data source: MEDLINE, CINAHL, Embase, PsycINFO, Scopus and ERIC (1995 and 2021) and reference lists were hand-searched. Review methods: The first author conducted a review of the titles and abstracts based on inclusion and exclusion criteria. All authors then reviewed and discussed each paper to determine inclusion. Qualitative appraisal using the Mixed-Methods Appraisal Tool was conducted, and all evidence from the quantitative, qualitative, and mixed-methods studies was identified and thematically analysed using a convergent qualitative synthesis design. Results: Ten papers were identified for review (six qualitative studies, two quantitative studies and two mixed methods studies). Inconsistencies in the inclusion criteria for older adults limited opportunities to explore the benefits for people with or without dementia. Few studies described the process of programme design, and there were wide variations in programme delivery. Programmes ranged from six weeks to eight months with a variety of activities and interactions implemented. Engaging in intergenerational programmes resulted in improved wellbeing and perceptions of social inclusion and reduced ageism. No correlations between programme design and impact were identified. Conclusions: Intergenerational programmes have important socio-emotional benefits for both adolescents and older adults. There is limited understanding of what meaningful intergenerational engagement entails as there is a lack of transparency surrounding the mechanics behind the programmes that are associated to positive change in the literature. In addition, there is currently no evidence of the longitudinal impacts or the broader social implications of these types of interventions. Future research is needed to explore programme design, the longitudinal effects, and the wider impacts of intergenerational programmes at a community and societal level. Tweetable abstract: Design and impact of intergenerational engagement between adolescents and older adults in the nursing home setting: a systematic review.